SOVEREIGNTY VS INTERNATIONAL COOPERATION: MAJOR PROBLEMS FACING EAST ASIA AT PRESENT - Miyazaki, Takashi (UI Scholars Hub, 2015)
World is now becoming united in which international community cannot live independently. The sovereignty of every States in the world cannot walk alone without having taken into consideration on the others States’ need and sovereignty. There are important issues of state sovereignty vs. international cooperation in regard of some grave problems facing our region, East Asia and even the world beyond. Among these issues are. the island disputes, humanitarian intervention, TPP and trade and economic integration in general, including RCEP advocated by Indonesia, also global warming. All of these issues cannot be solved without international cooperation. Thus international cooperation is a must in the borderless era as we are experiencing today.